Sustainability And Planning. Thinking and Acting According to Thermodinamics Laws - Leone, Antonio; Gobattoni, Federica; Pelorosso, Raffaele (TeMA - Journal of Land Use, Mobility and Environment, 2014)
The paper deals with environmental sustainability, in terms of intrinsic vulnerability and thermodynamics laws concepts, applied to urban green infrastructures. This approach gives also the track to build more resilient and complex landscapes. Integrating intrinsic vulnerability and thermodynamics laws concepts, an effective strategy could be conceived to face best management practices in planning more sustainable and healthy cities.